Almost-periodic solutions of an almost-periodically forced wave equation - Rui, Jie; Liu, Bingchen (Journal of mathematical analysis and applications, 2017)
This work focuses on a wave equation with almost-periodic forcing ψ(ωt,x) subject to Dirichlet boundary conditions. For the equation we obtain almost-periodic solutions corresponding to full-dimensional invariant tori of an associated infinite dimensional dynamical system. The proof is based on the reducibility via an improved KAM theory.